2012
DOI: 10.1063/1.3691113
|View full text |Cite
|
Sign up to set email alerts
|

Forming delocalized intermediate states with realistic quantum dots

Abstract: Articles you may be interested inEffect of quantum dot position and background doping on the performance of quantum dot enhanced GaAs solar cells Appl. Phys. Lett. Electron-hole recombination properties of In 0.5 Ga 0.5 As / GaAs quantum dot solar cells and the influence on the open circuit voltage Appl. Phys. Lett. 97, 123505 (2010); 10.1063/1.3492836 Carrier recombination effects in strain compensated quantum dot stacks embedded in solar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Recently, Reid et al showed for realistic QDs that the formation of a subband strongly depends on the QD uniformity [7]. Furthermore, the built-in potential in the intrinsic region of the solar cell unavoidably lifts the approximate degeneracy between the QD electron eigenenergies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Reid et al showed for realistic QDs that the formation of a subband strongly depends on the QD uniformity [7]. Furthermore, the built-in potential in the intrinsic region of the solar cell unavoidably lifts the approximate degeneracy between the QD electron eigenenergies.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the carrier escape mechanism is crucial to further improving the device performance. 42,43 Sellers et al 42 have evaluated the carrier escape mechanism in InAs/GaAs QDSC by using photocurrent measurements under sub-bandgap illumination. The 1.17-eV photon source and 0.8-eV photo source were chosen, and their fluencies were varied to reveal the fundamental carrier escaping principle.…”
Section: Carrier Escape Nature and Electric Field Effectmentioning
confidence: 99%